Outlook of Cassava Brown Streak Disease Assessment: Perspectives of the Screening Methods of Breeders and Pathologists - Ozimati, Alfred A.; Esuma, Williams; Alicai, Titus; Jannink, Jean-Luc; Egesi, Chiedozie; Kawuki, Robert (Frontiers in Plant Science, 2021)
Cassava production and productivity in Eastern, Central, and Southern Africa is ravaged by cassava brown streak disease (CBSD), causing yield losses of up to 100% when susceptible varieties are grown. Efforts to develop CBSD resistant clones are underway. However, the methods for screening CBSD resistance currently varies between breeders and pathologists, with limited empirical data to support their choices. In this study, we used empirical CBSD foliar and root necrosis data from two breeding populations termed as cycle zero (C0) and cycle one (C1) to assess and compare the effectiveness of breeder’s versus pathologist’s CBSD screening methods. Estimates of broad-sense heritability (H2) for breeder’s CBSD root necrosis assessment ranged from 0.15 to 0.87, while for pathologist’s assessment method, H2 varied from 0.00 to 0.71 in C0 clones. On the other hand, marker-based heritability estimates (h2) for C0 ranged from 0.00 to 0.70 for the breeder’s assessment method, and from 0.00 to 0.63 for the pathologist’s assessment method. For cycle one (C1) population, where both foliar and root necrosis data were analyzed for clones assessed at CETs and AYTs, H2 varied from 0.10 to 0.59 for breeder’s assessment method, while the H2 values ranged from 0.09 to 0.35 from pathologist’s CBSD computation method. Generally, higher correlations were recorded for foliar severity from the breeder’s assessment method (r = 0.4, p ≤ 0.01 for CBSD3s and r =0.37, p ≤ 0.01 for CBSD6s) in C1 clones evaluated at both clonal and advanced breeding stages than from the pathologist’s approach. Ranking of top 10 C1 clones by their indexed best linear unbiased predictors (BLUPs) for CBSD foliar and root necrosis, showed three overlapping clones between clonal and advanced selection stages for breeder’s method, meanwhile, only a clone featured in both clonal and advanced selection stages from pathologist’s CBSD assessment method. Overall, the breeder’s CBSD assessment method was more effective than the pathologist’s assessment method, and thus justifies its continued use in CBSD resistance breeding